Hyperlipidemia as a risk factor of renal allograft function impairment - Carvalho, MFC; Soares, V (Munksgaard Int Publ Ltd, 2001)
In this study, the graft outcome in renal allograft recipients with [high cholesterol group (HCG), n = 30] or without [normal cholesterol group (NCG), n = 42] hypercholesterolemia and with [high triglyceride group (HTG), n = 33] or without [normal triglyceride group (NTG), n = 36] hypertriglyceridemia were prospectively compared. At 6 months post-transplantation, no significant difference was observed between the groups (NTG compared with HTG, and NCG compared with HCG) regarding age, presence of arterial hypertension, kind of donor (living related or cadaveric), immunosuppressive therapy, number of rejection episodes per patient, frequency of patients with acute cellular rejection, prevalence of patients with diabetes mellitus or proteinuria > 3 g/24 h, and mean serum creatinine. The probability of doubling serum creatinine during follow-up was statistically different between NTG and HTG (12 months: NTG = 0.03, HTG = 0.15; 36 months: NTG = 0.08, HTG = 0.33; 60 months: NTG = 0.08, HTG = 0.48; and 120 months: NTG = 0.18, HTG = 0.48), but not between NCG and HCG (12 months: NCG = 0.05, HCG = 0.13; 36 months: NCG = 0.13, HCG = 0.24; 60 months: NCG = 0.19, HCG = 0.31; 84 months: NCG = 0.27, HCG = 0.31). There was no significant difference in actuarial graft survival between HCG and NCG or between NTG and HTG. Hypertriglyceridemia, but not hypercholesterolemia, was associated with loss of graft function.
Keywords: dyslipidemia; hypercholesterolemia; hypertriglyceridemia; kidney transplantation; renal allograft